Thermoluminescence response of Ce doped CaTiO3 nanophosphor synthesized by hydrothermal method for gamma dosimetry - Taqmeem Hussain (22224523) (2024)
Nanocrystalline calcium titanate (CaTiO3) doped with cerium ions (0.02 mol%) was synthesized via hydrothermal method and its luminescent properties were studied for gamma dosimetry. For the synthesized samples, the best luminescent response was achieved after annealing at 700 °C for 8 h. The synthesis was confirmed via XRD technique yielding the cyrstallite size of 22 nm for the most intense peak (121). The surface morphology was studied via scanning electron microscopy (SEM) yielding the grain size of 12 µm. The strong IR absorptions appeared at 700 cm−1 and 712 cm−1 attributed to bending mode of vibrations changing angle between Ti–O–Ti for CaTiO3 and CaTiO3:Ce respectively, as confirmed via Fourier-Transform Infrared (FTIR) Spectroscopy. Thermoluminescent (TL) response of undoped and doped samples was studied by Mikrolab RA94 TLD Reader-Analyzer having heating rate 10 °C/s, for absorbed doses 0–20 mGy from 137Cs γ-source having a dose rate 100 mSv/h. The found values at 662 keV for the photon-sensing parameters, i.e., mass attenuation coefficients (μ/ρ), mass-energy attenuation coefficient (μ en/ρ), effective atomic number for photon interaction (Zeff,PI) and effective atomic number for total photon energy absorption (Zeff,PEA) were 0.07030882 cm2/g, 0.0280245 cm2/g, 13.9 and 13.4 respectively. Thus, synthesized nanophosphor has shown excellent thermoluminescent dosimetric response for gamma radiation sensing in the selected dose range. Other Information Published in: Radiochimica Acta License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1515/ract-2024-0282